Antibiotic Treatment of Pertussis: Are 7 Days Really Sufficient?. Issue 4 (April 2015) - Dierig, Alexa; Beckmann, Christiane; Heininger, Ulrich
Abstract : Short courses of antibiotic therapy are recommended for treatment of pertussis. We report 2 young unvaccinated infants with persistently positive Bordetella pertussis by polymerase chain reaction from nasopharyngeal swabs despite 7 days of clarithromycin (15 mg/kg/d) therapy. In 1 patient, quantitative polymerase chain reaction was 7.02 (log GEq/mL) at the onset of treatment, 6.26 at the end of treatment and remained positive with 2.64 and 2.69 during and after a second 7-day course, respectively. The generally believed assumption that contagiousness of pertussis is terminated after 5 days of antibiotic treatment should be challenged, at least in young infants.